Directional and oscillating residual stress on the mesoscale in additively manufactured Ti-6Al-4V. (15th April 2019) - Strantza, M.; Vrancken, B.; Prime, M.B.; Truman, C.E.; Rombouts, M.; Brown, D.W.; Guillaume, P.; Van Hemelrijck, D.
Abstract: In additive manufacturing of metals as compared to conventional processing, the directional track-by-track and layer-by-layer nature of the fabrication process can lead to residual stresses that locally are both directionally and spatially heterogeneous. Much of the existing literature has focused either on the macroscale residual stress inside the entire part, or on the microscale residual stresses that are created around a scan vector, thereby neglecting the intermediate length-scale of the different layers. The objective of this research is to investigate such mesoscale residual stress distributions across several layers in Ti-6Al-4V components produced by laser metal deposition process. The incremental centre hole drilling and incremental slitting methods provide measurements with excellent spatial resolution within and across the layer length scale. In this work, the two methods complemented each other to quantify both mesoscale and directional variations of residual stress that correlate with the deposition pattern. Our findings also provide strong evidence that an oscillatory residual stress variation persists even after thermal cycling that occurs during deposition of subsequent layers. Graphical abstract: Image 1